Time Delays in Grievance Arbitration - Ponak, Allen; Olson, Corliss (Relations industrielles / Industrial Relations, 1992)
This paper examines the issue of time delays in grievance arbitration. Previous studies, as well as new data from the Province of Alberta, show that delays are increasing and that the average grievance takes approximately one year from its filing to its resolution by an arbitrator. Factors associated with delay include use of three person boards (versus sole arbitrators), sector, and type of issue. A conclusing section discusses the implications of these findings.